The role of education in improving labor productivity in the manufacturing sector.: Systematic Analysis through a Comprehensive Literature Review Approach - Amahda Nur Aulia; Khoirul Sahita Rahma; Muhammad Ashroful Ardiansyah; Muhammad Yusuf Karim; Nina Farliana (Jurnal Riset Manajemen dan Bisnis, 2025)
Education plays a crucial role in enhancing labor productivity, particularly in the manufacturing sector, which requires high levels of skill and workplace efficiency. This research aims to analyze the influence of education on labor productivity through a comprehensive literature review approach. Various national and international literature were systematically studied to understand how the education level contributes to skill improvement, innovation, and labor efficiency. The findings show that workers with higher education levels tend to have a better understanding of technology, can adapt to industrial changes, and contribute more significantly to production efficiency. Studies in Indonesia indicate a positive correlation between education level and labor productivity in the manufacturing sector, with productivity increases of 5-15% for each higher level of education. Additionally, investment in education has proven to have a positive impact on company competitiveness and overall economic growth. This research recommends the need for education policies aligned with industry needs, strengthening link and match programs, and improving vocational curriculum quality to create a competent and adaptive workforce in the Industrial Revolution 4.0 era.